2019
DOI: 10.5539/gjhs.v11n12p45
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Air Pollution (Carbon Dioxide and Total Volatile Organic Compound) and Pulmonary Disorders in Junior High School Students in Depok, West Java

Abstract: Good indoor air quality in the school environment is crucial for health and productivity of the students. Indoor air pollution needs to be taken into consideration, given that one can spend 90% of their time indoor. CO2 and Total VOC is an indoor pollutant that causes pulmonary disorder. This research is to investigate the relationship between exposure of CO2, concentration, total VOC and pulmonary disorder in Junior High School students. This research used cross-sectional design conducted on March - May 2018.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
(35 reference statements)
0
5
1
Order By: Relevance
“…A similar study by Wispriyono et al . 10 on indoor air pollution in Jakarta reported lower indoor and outdoor NO 2 than our results. Other studies conducted in the United States and Brazil measured NO 2 in the school environment reported there was association of NO 2 in air and respiratory disorders.…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations
“…A similar study by Wispriyono et al . 10 on indoor air pollution in Jakarta reported lower indoor and outdoor NO 2 than our results. Other studies conducted in the United States and Brazil measured NO 2 in the school environment reported there was association of NO 2 in air and respiratory disorders.…”
Section: Discussioncontrasting
confidence: 85%
“…The same questionnaire was used in previous school studies in Depok, West Java. 10 , 18 The selected students were interviewed by researchers based on the questionnaire.…”
Section: Design and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Literacy, a crucial element of education, has lately received attention as a potential explanatory pathway following the publishing of results from tests of children literacy abilities conducted by the educational community of Pakistan where they estimate that only two deserts of Pakistan have almost five thousand asthma child patients and these have speaking and reading problems to their illness. Sajid and Fraidan (2019) have demonstrated that the forced expiratory volume in 1 second (FEV1) is the best spirometric test for assessing airway blockage and treatment response in acute asthma during reading and speaking time (Wispriyono, Yulaeva, Hartono, & Pratama, 2019). Wargocki, Wyon, Lynge-Jensen, and Bornehag (2008) have written that 1-3 FEV1 is the volume of air exhaled in one second from maximal inspiration.…”
Section: Introductionmentioning
confidence: 99%